A review on potential bioactive phytochemicals for novel therapeutic applications with special emphasis on mangrove species - Sayantani Mitra; Nabanita Naskar; Punarbasu Chaudhuri (Elsevier, 2021)
Background: Plant derived bioactive compounds are gaining attention worldwide owing to their benign nature and various therapeutic uses. Being highly productive and diverse ecosystem, mangroves are enriched with varied classes of phytochemicals that have immense importance in the field of natural product-based medicines.Purpose: This review was conceived with the idea of highlighting the research based on bioactive compounds obtained from mangrove ecosystem.Study design: An attempt has been made to find out the mangrove species, which have been reported for high phytochemical content along with other biological activity.Methods: Thorough literature search till 2020 was carried out using various scientific web-based search engines. Keywords used during the search has been discussed in detail in the main manuscript. Chemical structures were drawn using ChemDraw Professional 15.Results: Separation strategies adopted by different researchers have been evaluated thoroughly. A detailed phytochemical profiling obtained qualitatively from different mangrove species have been listed along with the bioactive compounds isolated from those species. Apart from these, other biopotency studies like antibacterial, antiviral, anticancer and radical scavenging activities of plant extracts are also discussed in detail.Discussions: An attempt was made to find out the bioactive potential of different mangrove species so that they can be used for therapeutic purposes. Apart from antioxidants, these natural classes of chemicals have also proven their antimicrobial activities against human, animal, and plant pathogens. Discussion has been done on application of mangroves in cancer therapy and on prospects of the phytochemicals in novel drug discovery. Deciphering the bioactivities of these species will provide new leads in discovering new therapeutic agents and unveiling the source of already known pharmacological compounds.